2013
DOI: 10.2131/jts.38.245
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exposure to diesel exhaust affects X-chromosome inactivation factor expression in mice

Abstract: -Several studies have shown effects of diesel exhaust (DE) on the central nervous system, but the mechanism is unclear. Fetal mice were exposed to whole DE (contains gases and particles) in an inhalation chamber, and cerebrum gene expression changes were examined by gene assay (microarray and quantitative real-time PCR). By microarray, upregulation of Xist, B-raf and Drwms2 were detected. Especially, mRNA expression of Xist was increased in a concentration-dependent manner in male and female mice. Xist (X-inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…A few recent studies have documented distinct changes in Xist expression in response to different stimuli. For example, increased Xist levels in the brain were observed when fetal mice were exposed to diesel exhaust [28]. Similar increases in Xist expression were also found in response to HDAC inhibitor treatment for breast cancer, or chemotherapy for ovarian cancer [29,30].…”
Section: Discussionmentioning
confidence: 80%
“…A few recent studies have documented distinct changes in Xist expression in response to different stimuli. For example, increased Xist levels in the brain were observed when fetal mice were exposed to diesel exhaust [28]. Similar increases in Xist expression were also found in response to HDAC inhibitor treatment for breast cancer, or chemotherapy for ovarian cancer [29,30].…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown that in utero exposure to higher concentrations of DE significantly reduces locomotion of male offspring [ 14 , 50 ]. Recently, the effects of in utero DE inhalation on the central nervous system of offspring have also been reported [ 14 , 15 , 50 52 ]. However, the majority of these studies used substantially higher exposure levels than that encountered in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…For females, most of expressions of X-linked genes are regulated by Xchromosome inactivation (XCI), which occurs during fetal period, and this mechanism is regulated by Xist and its antisense, Tsix. We have already reported that expressions of these genes are changed in fetal exposure to diesel exhaust in a concentration dependent manner in cerebrums (Kumamoto et al, 2013). To clarify the mechanisms of neurodevelopmental disorders by BPA, we exposed BPA to pregnant mice 8th World Congress on Developmental Origins of Health and Disease S333 and examined mRNA expression of X-chromosome inactivation factor, X-linked neurodevelopment related genes and epigenetical changes of these genes.…”
Section: Dohad13-1203mentioning
confidence: 99%